Receiving and Study of Nanostructured ZnO and ZnS - N.B. Danilevskaya; N.V. Moroz; B.D. Nechyporuk; B.P. Rudyk (Журнал нано- та електронної фізики)
The possibility of obtaining zinc oxide and sulfide nanocrystals by electrolytic method using sodium thiosulfate solution as the electrolyte is given. Received samples were examined by methods of X-ray diffraction analysis and absorption spectrometry. The size of nanoparticles is defined by Williamson-Hall and Debye-Scherrer methods. Found that the nanocrystals data of substances are in tension, which affect the value of the broadening of x-ray peaks.